Эффективность информационно-библиотечного обслуживания в научно-исследовательских институтах и проектно-конструкторских бюро - Воверене, Она (Knygotyra, 1985)
In the article the development of the viewpoints on measuring the efficience of the information and library service at research institute and design bureau is considered.It is possible to classify all researches on the problem in two main groups.The first group is made up of researches in which the information and library services are considered as “service system” of the science. In these researches а proposition is made to measure the functional effectiveness of an information and library system according to the extent of satisfying the information requests; in the case of an automatic information retrieval system – according to the relevaance and recall factors of the information retrieved in answer to the request.In the researches of the second group the information activity is considered as an indispensible part of the research process. Depending on the participation degree of the information and library system in research and development works, it is proposed to evaluate the functional effectiveness of an information and library system in а research institute according to the extent of satisfying the information needs of specialists (executors of research and development works) bу the information service and the degree of the information and library services influence on the scientific and technical level of research and development works; and economic efficiency according to the criterion of time savings bу development specialists through freeing them from the retrieval, collection and analytico-synthetic information processing.